Monetary Economics - Jhingan, M.L. (Delhi: Vrinda Publications Ltd., 1997)
This book deals with money and banking. It provides a thorough exposition of the classical, Keynesian and modern monetary theories systematically and critically.
Includes bibliographical references
rua 18/07/2016
Loans
Keywords: Money; Monetary economics; Financial markets; Banking